Holding up the universe - Niven, Jennifer (New York : Ember, 2018)
Everyone knows Libby Strout. She's the girl who was so heavy she had to be lifted out of her house by a crane. After being homeschooled for years, she's ready to rejoin the human race, aka the junior class of MVB High. She's free, she's strong, and she's going to get through this or so she lies to herself. (Okay, fine, she s terrified out of her skull.)
Keywords: Prosopagnosia -- Juvenile fiction; Love stories